Predation drives local adaptation of phenotypic plasticity. Issue 1 (January 2018) - Reger, Julia; Lind, Martin; Robinson, Matthew; Beckerman, Andrew
Abstract Phenotypic plasticity is the ability of an individual genotype to alter aspects of its phenotype depending on the current environment. It is central to the persistence, resistance and resilience of populations facing variation in physical or biological factors. Genetic variation in plasticity is pervasive, which suggests its local adaptation is plausible. Existing studies on the adaptation of plasticity typically focus on single traits and a few populations, while theory about interactions among genes (for example, pleiotropy) suggests that a multi-trait, landscape scale (for example, multiple populations) perspective is required. We present data from a landscape scale, replicated, multi-trait experiment using a classic predator–prey system centred on the water fleaDaphnia pulex . We find predator regime-driven differences in genetic variation of multivariate plasticity. These differences are associated with strong divergent selection linked to a predation regime. Our findings are evidence for local adaptation of plasticity, suggesting that responses of populations to environmental variation depend on the conditions in which they evolved in the past. Genetic variation in phenotypic plasticity suggests local adaptation is possible. A multi-site, multi-trait experiment shows such adaptation driven by predation inDaphnia pulex .